MENYINGKAP HUBUNGAN AGAMA DAN FILSAFAT: MERENDA KESESATAN FILSAFAT AL-GHAZALI, MERESPONS KETERHUBUNGAN FILSAFAT DAN AGAMA IBNU RUSYD - Mas'udi, Mas'udi (Jurnal Penelitian, 2013)
THE RELATIONSHIP BETWEEN RELIGION AND PHILOSOPHY (Searching the Fallacy Philosophy of  al-Ghazali, Responding the Connection between Philosophy and Religion of  Ibn Rushd). Philosophy and religion are considered as the two entities as if  different. Religion is indicated on revelation as the primary foundation and affiliated to the principles of  normativity. Meanwhile, the philosophy is more leaning on the principles of rationality embodies the values of divinity rububiyyah in the historical domain. Necessarily, the two aspects above adhere to the principles of  various viewpoints. From these points, both of  them want to achieve the ultimate truth in interpreting the texts of  the Lord that is still abstract. Textuality and contextuality become the important determinants ultimately carried by the two segments of  thought. The originality of  religious doctrine becomes an important aspect which was presented by al-Ghazali in order to confront the world of philosophy-laden fiction. Philosophy and religion in the view of  al-Ghazali are the two different entities and existences. Meanwhile, Ibn Rushd struggled to establish the two entities and the existences of  this ijtihad which become an aspect that can be integrated. Both are struggling to find the truth.keywords: Philosophy, Religion, Theology, Logic, Confusion,.Filsafat dan agama dinilai sebagai dua entitas yang “seakan-akan” berbeda. Agama lebih berindikasi pada wahyu sebagai landasan primernya dan berafiliasi pada prinsip-prinsip normativitas. Sementara itu, filsafat yang lebih berhaluan pada prinsip-prinsip rasionalitas mewujudkan nilai-nilai ketuhanan rububiyyah dalam domain historis. Secara niscaya, kedua aspek di atas menganut prinsip-prinsip sudut pandang angle yang bervariasi. Dari variasi sudut pandang keduanya ingin mencapai suatu kebenaran hakiki dalam menafsirkan teks-teks Tuhan yang masih bersifat absrak. Tekstualitas dan kontekstualitas menjadi dua determinasi penting yang akhirnya diusung oleh kedua segmentasi  pemikiran  tersebut.  Pengusungan  orisinalitas  doktrin agama  menjadi  aspek  penting  yang  diketengahkan  al-Ghazali guna  mengkonfrontasi  dunia  filsafat  yang  sarat  rekaan.  Filsafat dan agama dalam pandangan al-Ghazali merupakan dua entitas dan eksistensi yang berbeda. Sementara itu, Ibnu Rusyd berjuang untuk mengukuhkan bahwa kedua entitas dan eksistensi ijtihad ini merupakan aspek yang dapat dipadukan. Keduanya berjuang untuk mencari suatu kebenaran.kata kunci: Filsafat, Agama, Teologi, Logika, Kerancuan, Hukum, Fikih.